QUADROS EM MOVIMENTO, ESQUADROS DA MEMÓRIA: MEMÓRIA, IMAGEM E PALAVRA EM JOSÉ DE ALENCAR - Mendes, Danielle (Revista de Letras, 2016)
QUADROS EM MOVIMENTO, ESQUADROS DA MEMÓRIA: MEMÓRIA, IMAGEM E PALAVRA EM JOSÉ DE ALENCAR